PREDICTION OF THE BUSINESS ORIENTATION BASED ONANALYSIS OF USER DESIRES - Anefiyayeva, Nurdaulet; Anefiyayeva, Dayana (Journal of Emerging Technologies and Computing, 2023)
Business is a well-established system aimed at making money and an activity that not everyone can succeed in. Business should work like clockwork that always works well with the most important - data. Only on the basis of data analysis can we make informed and rational decisions about where the business should develop, its methods became common in business whentechnologies for collecting and processing data developed. One of the maindecisions that can be taken on the basis of data processing is to predict in which area it is better to develop a business. This paper aims to build a correctunderstanding of what customers are interested in based on feedback fromcustomers. Improved machine learning solves this problem and algorithms like decision trees, neural networks, and regression are used to analyze issues and choose the best option - a foundation for the future strategy of the company.